Pengaruh Opini Audit, Ukuran Kap, Profitabilitas dan Kompleksitas Operasi Perusahaan Terhadap AUDIT Reportlag Pada Perusahaan Pertambangan Yang Terdaftar Di BEI(Periode 2013-2015) - Damayanti, Yunisdha Nuvika; , Drs. Atwal Arifin, M.Si., Akt, CA (2017)
This study aimed to analyze the influence of the audit opinion, the size of the hood, profitability and complexity of the company's operations to the audit reportlag in mining companies listed on the Stock Exchange (period 2013-2015). The population used in this study are all mining companies listed on the Indonesia Stock Exchange in 2013-2015 totaling 39 companies. The sampling technique used purposive sampling method. Based on predetermined criteria, obtained a sample of 13 companies with the observation period of 3 years. The analytical method used in this research is multiple linear regression analysis. The results showed an audit opinion, profitability, and industry type do not affect the audit reportlag as evidenced by the significant value of more than 0.05. While the size of the hood, and the complexity of the audit reportlag effect as evidenced by the significant value of less than 0.05.